PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR BIOLOGI KELAS X-7 SMA N 1 BARAT MELALUI PENERAPAN MODEL THINK PAIR SHARE - Purwanti, Nunuk (Jurnal Florea, 2015)
Motivation plays an important role in learning, X-7 grade students of SMA Negeri 1 Barat shows theknown to be less motivated to follow the teaching of Biology. The aim of research to increase themotivation to learn biology X - 7 grade SMA Negeri 1 Barat with the application Think Pair Share(TPS). This type of research is classroom action research with planning, action, observation, andreflection, material monera and protists conducted in two cycles. Research subject class X-7 SMANegeri 1 Barat of academic year 2014/2015. The results showed cooperative learning Think Pair Sharecan help students overcome the problem for expression and enhance self-confidence of students, so asto increase the motivation of students.Keywords: motivation to learn, think pair share